Hoạt tính gây độc tế bào và kháng vi sinh vật kiểm định của một số dẫn xuất bengamide - Đào, Phí Thị; Mai Hương, Đoàn Thị; Lợi, Vũ Văn; Huệ, Nguyễn Thị; Cường, Phạm Văn (Vietnam Journal of Chemistry, 2017)
The bengamides comprise a family of marine natural products first isolated by Crews et al. from Jaspis sponges indigenous to the coral reefs that surround the Fiji islands. These fused ketide-amino acid derivatives are potent antiproliferative agents against both transformed and nontransformed cells. These interesting biological activities have made bengamides popular targets for synthesis and biological studies. Several syntheses of bengamides A, B, and E have been previously published. In this study, we synthesized 9a-9d from the commercial available D-ornithine (HCl) (3) and α-D-glucoheptonic γ-lactone using microwave irradiation assistance. Cytotoxic evaluation of the compounds 9a-9d against six cancer cell lines (KB, LU-1, HepG-2, MCF-7, HL60 and Hela) indicated that compounds 9d was more sensitive toward Lu-1, HepG2 and KB. Compounds 9c-9d were found to have antibacterial activity against E. faecalis, S. aureus, B. cereus and C. albicans with a MIC value of 4-256 µg/ml. Keywords. Bengamide, Jaspis sponge, cytotoxic activity, antimicrobial.